2022
DOI: 10.3892/ijmm.2022.5195
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal STAT1 derived from high phosphorus‑stimulated vascular endothelial cells induces vascular smooth muscle cell calcification via the Wnt/β‑catenin signaling pathway

Abstract: Vascular calcification is commonly observed in chronic kidney disease. The mechanism of how the calcification signal from endothelial cells is transmitted to vascular smooth muscle cells (VSMCs) remains unknown. The aim of the present study was to investigate whether exosomes from HUVECs (HUVEC-Exos) could regulate VSMC calcification and its potential signaling pathway. HUVEC-Exos were isolated from HUVECs under no phosphorus (NP) and high phosphorus (HP) conditions. Alizarin Red S staining and calcium (Ca) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…To verify our findings, we used fludarabine, which has shown to be a specific STAT1 inhibitor in previous studies 30 , 31 . It is currently used clinically as chemotherapy to treat chronic lymphocytic leukemia 32 .…”
Section: Resultsmentioning
confidence: 61%
“…To verify our findings, we used fludarabine, which has shown to be a specific STAT1 inhibitor in previous studies 30 , 31 . It is currently used clinically as chemotherapy to treat chronic lymphocytic leukemia 32 .…”
Section: Resultsmentioning
confidence: 61%
“…Deleted Deleted However, which component in ADSC-Exos may play a role in activating Wnt/βcatenin signaling pathway still remains unspecified and needs further exploration. Even though numerous previous studies have shown that a variety of effective substances (e.g., miR-424-5p, miR-1260b, miR-127-3p, miR-218-5p, miR-22-5p, miR-181a-5p, and miR-148b-3p [54,58]; protein Hic-5, UBR2, and STAT1 [59][60][61][62][63][64][65]) in exosomes from the different sources can regulate the Wnt/β-catenin signaling pathway, single miRNA or protein from exosomes might not completely recapitulate the regulatory effects. Therefore, in the present study, instead of exosomal miRNAs or proteins, we used exosomes as a whole to investigate the therapeutic effects on AGA.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al demonstrated that STAT1-rich exosomes secreted by HP-treated HUVECs are delivered to VSMCs, thus promoting VSMC calcification through the activation of Wnt/β-catenin signaling. This result indicates that HP-HUVEC-Exo has calcium-promoting effects [ 87 ]. In addition to target proteins, miRNAs encapsulated in EC-EVs have been demonstrated to modulate blood vessels in CKD-MBD, with miR-143-3p and miR-145-5p inhibiting VC and miR-221-3p and miR-222-3p enhancing VC [ 88 ].…”
Section: Reviewmentioning
confidence: 99%